2006
DOI: 10.1074/jbc.m604684200
|View full text |Cite
|
Sign up to set email alerts
|

p21WAF1/Cip1 Suppresses Keratinocyte Differentiation Independently of the Cell Cycle through Transcriptional Up-regulation of the IGF-I Gene

Abstract: p21 plays a dual role in keratinocyte growth and differentiation control. It restricts the number of keratinocyte stem cell populations while inhibiting the later stages of differentiation independently of the cell cycle. The molecular/biochemical mechanism for the differentiation suppressive function of p21 is unknown. Here we show that elevated p21 expression leads to activation of MAPK family members in a keratinocyte-specific and cell cycle-independent manner, and up-regulation of MAPK activity can explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 42 publications
2
42
1
Order By: Relevance
“…This discrepancy is probably due to more potent structure-specific PPAR-independent activity ('off-target' effects) of ciglitazone and troglitazone than rosiglitazone and pioglitazone (15). Previous studies suggested that such strong off-target effects can reduce cornification marker expression in keratinocytes during later stages of differentiation via p63-mediated sustained p21 expression (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy is probably due to more potent structure-specific PPAR-independent activity ('off-target' effects) of ciglitazone and troglitazone than rosiglitazone and pioglitazone (15). Previous studies suggested that such strong off-target effects can reduce cornification marker expression in keratinocytes during later stages of differentiation via p63-mediated sustained p21 expression (16)(17)(18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Cip1 was originally known as a mediator of p53-induced growth arrest; however, there is increasing evidence that, depending on the tissue, this protein is rather involved in cell proliferation, as has been shown in keratinocytes (Devgan et al 2006) and in intestinal epithelial cells using p27 kip1 and p21 Cip1 conditional knockout mice (Stehr et al 2005). The association of b-catenin within cell-cell junctions in differentiated cells ongoing conformational changes (Manin et al 2000) may explain the reduction of functionally competent p53 through an ubiquitin-mediated proteolysis, since b-catenin can no longer interact with p53 and interfere with the normal proteasomal degradation (Damalas et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of p21 WAF was doubly attractive, as p21 WAF possesses roles in keratinocyte differentiation (Topley et al, 1999) separate to that of cell cycle regulation (Devgan et al, 2006) and can be an early response to PTEN loss (Yoo et al, 2006). All HK1.fos/Δ5Pten flx KAs exhibiting P-GSK3β hyper-inactivation and high p53 expression also exhibited novel high p21 WAF expression levels (Fig.…”
Section: Hk1fos/δ5ptenmentioning
confidence: 99%
“…Given the roles for p21 WAF in epidermal differentiation (Topley et al, 1999), this basal layer expression of p21 WAF would be consistent with the premature commitment of HK1.fos/ΔPten flx keratinocytes to terminal differentiation, as indicated by novel basal layer K1 expression (above). The confused atypical nature of epidermal differentiation, however, may be due to continued, p21 WAF expression in the suprabasal/granular layers when normally p21 expression shuts down (Devgan et al, 2006).…”
Section: Hk1fos/δ5ptenmentioning
confidence: 99%
See 1 more Smart Citation